Prednisolone dosages in Addisonian dogs after integration of ACTH measurement into treatment surveillance - Zeugswetter, Florian K.; Haninger, Tanja (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
Objective: To examine the prednisolone and fludrocortisone dosages in dogs with primary hypoadrenocorticism after integrating endogenous ACTH (eACTH) determination into the surveillance regimen.Materials and methods: The local electronic medical records database was searched for dogs with primary hypoadrenocorticism and a complete follow-up including routine eACTH measurements until stabilisation. Dogs were considered stable if they showed no signs of glucocorticoid deficiency or excess, sodium and potassium were within the laboratory reference limits and no change of prednisolone and/or fludrocortisone dosage was recommended by the clinician. To avoid subclinical glucocorticoid overreplacement prednisolone was routinely reduced in case of eACTH concentrations below the detection limit of the assay.Results: Thirteen client-owned dogs were eligible for inclusion in the study. Stabilisation was achieved after a median (range) of 14 (1–36) months and 4 (2–9) visits. After exclusion of two patients that did not need additional glucocorticoids, the prednisolone dosage was 0.06 (0.02–0.26) mg/kg/day and 9.1 times lower than the starting dose. No correlation was identified between prednisolone dosage in mg/kg/day and bodyweight (rSP = –0.369, p = 0.215). The final fludrocortisone dose was 0.022 (0.013–0.036) mg/kg/day. The median (range) survival time of the dogs that had died during the study period (n = 6) and all dogs was 74.5 (62–98) months and 71 (18–104) months, respectively.Conclusion and clinical relevance: The integration of eACTH measurement into treatment surveillance helps to optimise glucocorticoid replacement therapy. It supports treatment recommendations and is a particular aid in dogs with ambiguous clinical signs. The results suggest that most dogs on fludrocortisone substitution therapy benefit from additional very low dose prednisolone.Ziel: Bestimmung der Prednisolonund Fludrocortison-Dosierungen bei Hunden mit primärem Hypoadrenokortizismus nach Integration der Messung von endogenem ACTH (eACTH) in die Therapieüberwachung.Material und Methoden: Im elektronischen Informationssystem des Tierspitals wurde nach Hunden mit Hypoadrenokortizismus gesucht, bei denen eine komplette Nachbetreuung inklusive regelmäßiger eACTHMessungen erfolgte und eine Stabilisation erreicht werden konnte. Die Patienten galten als stabil, wenn sie keine Symptome eines Glukokortikoidmangels oder -überschusses zeigten, Natriumund Kaliumkonzentration im Referenzbereich lagen und der behandelnde Tierarzt keine Therapieanpassung empfahl. Zur Vermeidung einer subklinischen Glukokortikoidüberdosierung wurde die Prednisolondosis bei einer eACTHKonzentration unterhalb der Nachweisgrenze weiter reduziert.Ergebnisse: Dreizehn Hunde aus Privatbesitz gingen in die Studie ein. Die Stabilisation wurde im Median (Range) nach 14 (1–36) Monaten und 4 (2–9) Visiten erreicht. Nach Ausschluss von zwei Patienten, die neben Fludrocortison keine zusätzlichen Glukokortikoide benötigten, lag die Prednisolondosierung bei 0,06 (0,02–0,26) mg/kg/Tag und war damit um das 9,1-Fache niedriger als die Anfangsdosis. Zwischen Prednisolondosis in mg/kg/Tag und Körpergewicht konnte keine Korrelation festgestellt werden (rSP = –0,369, p = 0,215). Die ermittelte endgültige Fludrocortisondosis betrug 0,022 (0,013–0,036) mg/kg/Tag. Die Überlebenszeit der zum Zeitpunkt der Datenerhebung verstorbenen sechs Hunde und die aller Hunde betrug 74,5 (62–98) bzw. 71 (18–104) Monate.Schlussfolgerung und klinische Relevanz: Die Integration der eACTH-Messung in die Therapieüberwachung hilft bei der Optimierung der Glukokortikoid-Substitutionstherapie, unterstützt Therapieempfehlungen und ist besonders wertvoll bei Hunden mit unklaren klinischen Befunden. Die Resultate legen nahe, dass die meisten Patienten mit Fludrocortison-Substitutionstherapie von zusätzlichen sehr niedrig dosierten Prednisolongaben profitieren.
Keywords: Adrenocorticotropic hormone; hypoadrenocorticism; glucocorticoids; monitoring